Beyond Tuberculosis: A Rare Case of Mounier‐Kuhn Syndrome in an Ethiopian Woman With Chronic Cough and Bronchiectasis - Girma Deshimo; Enguday Demeke (Clinical Case Reports)
ABSTRACT This case highlights the importance of considering rare conditions like Mounier‐Kuhn Syndrome in patients with chronic respiratory symptoms, especially in regions with high tuberculosis prevalence. Enhanced awareness and advanced imaging are vital for accurate diagnosis and effective management of such conditions.